Implementasi Manajemen Kinerja Pegawai Pada Dinas Perpustakaan dan Arsip Kabupaten Bintan - Dinda Meirany; M. Dinur Ikhsan; Sigit Danianto; Yuniati Nur Puspitasari; Satriadi Satriadi (Jurnal Manajemen Kreatif dan Inovasi, 2024)
This study aims to analyze the implementation of public library service management in Bintan Regency Library and Archives Service. This study is a qualitative study. The results of the study show that although the implementation of library service management in Bintan Regency Library and Archives Services has been implemented, there are still barriers to implementation and it is not optimal. The Bintan Regency Library and Archives Service plan was successfully implemented through the implementation of technical guidance to staff. From an organizational perspective, the availability of facilities and infrastructure resources of Bintan Regency Library and Archives Services generally still does not meet the needs of all strata of society. Although implementation was carried out, it was not optimal due to lack of human resources, limited funding from Bintan Regency Library Archive Service for program implementation, and lack of reading book collection of Bintan Regency Library Archive Service. Supervision (control) indicates that supervision has been carried out through regular meetings, gradual supervision and monitoring of staff discipline, but the government has paid little attention to the development of public library functions.